Human parasitology - Bogitsh, Burton J. (Burton Jerome) (Elsevier Academic Press, 2005)
Annotation Human Parasitology emphasizes the medical aspects of the topic, while incorporating functional morphology, physiology, biochemistry, and immunology to enhance appreciation of the diverse implications of parasitism. Bridging the gap between classical clinical parasitology texts and traditional encyclopaedic treatises, Human Parasitology appeals to students interested not only in the medical aspects of Parasitology but also to those who require a solid foundation in the biology of parasites.*Updated and expanded reference section*New chapter on Immunology*Additional SEM and TEM micrographs*Professionally drawn life cycle illustrations*Addition of "Host Immune Response" section for each organism.